Global analyses revealed age‐related alterations in innate immune responses after stimulation of pathogen recognition receptors - Metcalf, Talibah U.; Cubas, Rafael A.; Ghneim, Khader; Cartwright, Michael J.; Grevenynghe, Julien Van; Richner, Justin M.; Olagnier, David P.; Wilkinson, Peter A.; Cameron, Mark J.; Park, Byung S.; Hiscott, John B.; Diamond, Michael S.; et al. (Aging cell, 2015)
Summary Aging leads to dysregulation of multiple components of the immune system that results in increased susceptibility to infections and poor response to vaccines in the aging population. The dysfunctions of adaptive B and T cells are well documented, but the effect of aging on innate immunity remains incompletely understood. Using a heterogeneous population of peripheral blood mononuclear cells (PBMCs), we first undertook transcriptional profiling and found that PBMCs isolated from old individuals (≥ 65 years) exhibited a delayed and altered response to stimulation with TLR4, TLR7/8, and RIG‐I agonists compared to cells obtained from adults (≤ 40 years). This delayed response to innate immune agonists resulted in the reduced production of pro‐inflammatory and antiviral cytokines and chemokines including TNFα, IL‐6, IL‐1β, IFNα, IFNγ, CCL2, and CCL7. While the major monocyte and dendritic cell subsets did not change numerically with aging, activation of specific cell types was altered. PBMCs from old subjects also had a lower frequency of CD40+ monocytes, impaired up‐regulation of PD‐L1 on monocytes and T cells, and increased expression of PD‐L2 and B7‐H4 on B cells. The defective immune response to innate agonists adversely affected adaptive immunity as TLR‐stimulated PBMCs (minus CD3 T cells) from old subjects elicited significantly lower levels of adult T‐cell proliferation than those from adult subjects in an allogeneic mixed lymphocyte reaction (MLR). Collectively, these age‐associated changes in cytokine, chemokine and interferon production, as well as co‐stimulatory protein expression could contribute to the blunted memory B‐ and T‐cell immune responses to vaccines and infections.